Psia Kość! Linguistic creativity in the names of board and card games - Furmaniak, Katarzyna (Linguistic creativity in marketing, 2022)
This article describes the names of board and card games that were used in order to attract new players. Among the signs of linguistic creativity are neologisms (such as lexical blends); using graphic devices; retrieving the literal meaning of the idiomatic phrases; replacement innovations (phraseological, for example); using intertextuality.